Clinical characteristics and influencing factors of cardiovascular comorbidities in psoriasis - Dai, Xinrui; Qin, Xiaoyue; Li, Zongyang (Frontiers in Cardiovascular Medicine, 2025)
IntroductionPsoriasis is a chronic inflammatory skin disorder with systemic implications, including an elevated risk of cardiovascular disease (CVD). The interaction between psoriasis severity, metabolic abnormalities, and systemic inflammation may contribute to cardiovascular comorbidities. However, the clinical characteristics and predictors of CVD in psoriasis patients remain incompletely understood.MethodsWe conducted a retrospective cohort study of 320 adult patients with psoriasis. Participants were categorized into two groups according to cardiovascular status (psoriasis with CVD vs. psoriasis without CVD). Demographic, clinical, metabolic, and inflammatory parameters were compared. Variable selection was performed using LASSO regression, followed by multivariable logistic regression to identify independent predictors of CVD. Kaplan–Meier curves and Cox proportional hazards models were applied to evaluate survival outcomes.ResultsAmong 320 psoriasis patients, 88 (27.5%) had cardiovascular comorbidities. Compared with controls, patients with CVD were significantly older, had longer psoriasis duration, higher body mass index, and more severe disease (mean PASI 12.8 vs. 9.7, p < 0.001). They also exhibited higher prevalence of hypertension (68.2% vs. 20.7%), diabetes (25.0% vs. 10.3%), and dyslipidemia (50.0% vs. 22.4%), as well as elevated C–reactive protein levels. Multivariable regression identified older age, longer disease duration, higher PASI scores, hypertension, diabetes, and CRP as independent predictors of CVD. Kaplan–Meier analysis showed that severe psoriasis combined with hypertension conferred the greatest risk, with a significantly lower CVD–free survival probability (adjusted HR: 3.56, 95% CI: 2.01–6.31).DiscussionPsoriasis patients with cardiovascular comorbidities demonstrate a distinct clinical and inflammatory profile. Our findings underscore the importance of integrated management, with aggressive control of both psoriasis severity and traditional risk factors to mitigate cardiovascular burden. Future prospective studies should evaluate whether targeted anti–inflammatory therapies can reduce cardiovascular outcomes in psoriasis.